Incidence and mortality of lung cancer: global trends and association with socioeconomic status. Issue 1 (December 2017) - Wong, Martin; Lao, Xiang; Ho, Kin-Fai; Goggins, William; Tse, Shelly
Abstract We examined the correlation between lung cancer incidence/mortality and country-specific socioeconomic development, and evaluated its most recent global trends. We retrieved its age-standardized incidence rates from the GLOBOCAN database, and temporal patterns were assessed from global databases. We employed simple linear regression analysis to evaluate their correlations with Human Development Index (HDI) and Gross Domestic Product (GDP) per capita. The average annual percent changes (AAPC) of the trends were evaluated from join-point regression analysis. Country-specific HDI was strongly correlated with age-standardized incidence (r = 0.70) and mortality (r = 0.67), and to a lesser extent GDP (r = 0.24 to 0.55). Among men, 22 and 30 (out of 38 and 36) countries showed declining incidence and mortality trends, respectively; whilst among women, 19 and 16 countries showed increasing incidence and mortality trends, respectively. Among men, the AAPCs ranged from −2.8 to −0.6 (incidence) and −3.6 to −1.1 (mortality) in countries with declining trend, whereas among women the AAPC range was 0.4 to 8.9 (incidence) and 1 to 4.4 (mortality) in countries with increasing trend. Among women, Brazil, Spain and Cyprus had the greatest incidence increase, and all countries in Western, Southern and Eastern Europe reported increasing mortality. These findings highlighted the need for targeted preventive measures.